An approach to the problems and questions of musical analysis from a historical perspective (Per Musi, 2020)
This paper wishes to approach, from a historical perspective, some of the ideals or goals that musical analysis has taken into account for the treatment of the musical work as an object of study. From an approach to music as an object, to the metalanguages that refer to that object and of course, to the different methodologies to approach it, a critical reflection is built on the transformations that the practice of musical analysis has undergone, including its expansion processes through multiple dialogical relations with other fields of knowledge. The aim of this critical approach is to contribute to the reflection on the current dilemmas of the practice of musical analysis and, above all, to the teaching of analysis in higher musical education.